2020
DOI: 10.1021/acs.iecr.0c04292
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Characteristics of Typical Ni–Cr Alloys and Ni–Cr–Mo Alloys in Supercritical Water: A Review

Abstract: The corrosion of supercritical water system materials under high-temperature and high-pressure conditions exists widely, which may result in the serious damage of the supercritical water reactor. Therefore, the improvement of the corrosion resistance of reactor material is important for ensuring the serviceability of the supercritical water reactor. This article provides a comprehensive and updated review on the corrosion characteristics of Ni−Cr and Ni−Cr−Mo corrosion-resistant alloys in supercritical water, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…These results [ 36,40 ] show that Fe ions diffuse into the lattice of the spinel in a substitution process to yield NiFe x Cr 2‑x O 4 in the outer layer oxide. [ 35 ] They also reported a beneficial effect of Mo (and W) on the repassivation behavior of local active—as well as widespread transpassive—corrosion sites. [ 36 ]…”
Section: Oxide Formation On Nickel‐based Alloysmentioning
confidence: 99%
“…These results [ 36,40 ] show that Fe ions diffuse into the lattice of the spinel in a substitution process to yield NiFe x Cr 2‑x O 4 in the outer layer oxide. [ 35 ] They also reported a beneficial effect of Mo (and W) on the repassivation behavior of local active—as well as widespread transpassive—corrosion sites. [ 36 ]…”
Section: Oxide Formation On Nickel‐based Alloysmentioning
confidence: 99%
“…One of key obstacles for the large-scale commercialization of SCWO is reactor corrosion, which is caused by reactive free radicals, strong acids and inorganic salts formed in reactions, and high concentrations of oxygen dissolved in supercritical water [4]. Chemical corrosion occurs mainly in low-density supercritical areas including back-end of the preheater, the front-end of the reactor and cooler), while electrochemical corrosion appears in subcritical and high-density supercritical areas such as the front-end of the preheater and the back-end of the cooler [5]. The corrosion problem affects normal operating of reaction system and shortens reactor life due to the penetration through tube wall caused by general corrosion, heat transfer deterioration caused by oxide growth, stress corrosion cracking, and stress exceeding the material yield limit [6].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been conducted to evaluate the corrosion resistance of different candidate materials under aggressive environments for the fuel cladding and other water‐bearing components in SCWR 2,3,7–21 . Many excellent reviews summarize some of the common corrosion phenomena and described the predominant corrosion mechanisms in SCW 22–25 . The results revealed that the corrosion rate is related to the content of different elements (Cr and Ni) and the working condition such as temperature and pressure of the SCW.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Many excellent reviews summarize some of the common corrosion phenomena and described the predominant corrosion mechanisms in SCW. [22][23][24][25] The results revealed that the corrosion rate is related to the content of different elements (Cr and Ni) and the working condition such as temperature and pressure of the SCW.…”
Section: Introductionmentioning
confidence: 99%